2000
DOI: 10.1292/jvms.62.905
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction(PCR) for the Detection of Herpesvirus in Tortoises.

Abstract: ABSTRACT. A polymerase chain reaction (PCR)-based method using a herpesvirus consensus primer was assessed for the identification of herpesviral infections in tortoises. A single band of about 230 bp was detected in PCR products from two out of twenty swabs taken from the oral cavity, three out of three paraffin-embedded tissue sections from the liver (two cases) and oral mucosa (one case), and one out of two fresh tissue samples from the oral mucosa. Nucleotide sequencing of these PCR products indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…The sequence information available is, however, generally limited to a small portion of the DNA polymerase gene. Analysis of this short fragment supports the classification of chelonian HVs in the subfamily Alphaherpesvirinae of the family Herpesviridae [57,61,62,6669]. It has been suggested that the chelonian HVs form a monophyletic group typical of other genera in the family Herpesviridae , and that these viruses be classified together in a new genus with the suggested name “Chelonivirus” [57].…”
Section: Herpesviridaesupporting
confidence: 60%
See 2 more Smart Citations
“…The sequence information available is, however, generally limited to a small portion of the DNA polymerase gene. Analysis of this short fragment supports the classification of chelonian HVs in the subfamily Alphaherpesvirinae of the family Herpesviridae [57,61,62,6669]. It has been suggested that the chelonian HVs form a monophyletic group typical of other genera in the family Herpesviridae , and that these viruses be classified together in a new genus with the suggested name “Chelonivirus” [57].…”
Section: Herpesviridaesupporting
confidence: 60%
“…A revised method of naming newly described and characterized chelonian HVs, particularly HVs of tortoises, has therefore been used in recent publications. The first tortoise HV from which sequence data from a small portion of the DNA polymerase gene became available, allowing a preliminary taxonomic analysis of the isolate, was from Russian and pancake tortoises ( Testudo horsfieldii and Malacochersus tornieri ) in Japan [69]. Studies on HVs from European tortoises showed that similar viruses can also be found in Russian tortoises in Europe, but that these viruses differ from the majority of isolates found in Mediterranean tortoises kept as pets in Europe, building two distinct genogroups [62].…”
Section: Herpesviridaementioning
confidence: 99%
See 1 more Smart Citation
“…9,20,21,24,[31][32][33] PCR likewise has proven to be a powerful tool for the retrospective detection of viral nucleic acid in paraffinized brain tissues. 12,24,32,[34][35][36] In this study, we used degenerate herpes-and adenoviral PCR and a specific canine parvovirus PCR to study paraffinized brain tissues from dogs that died from NME, NLE, or GME.…”
Section: Discussionmentioning
confidence: 99%
“…An 181-bp region obtained from the ToHV using nested PCR was further analyzed by nucleotide sequencing and indicated that this tortoise virus is a new type of her- pesvirus. 12 However, such a small region of sequence data was not always sufficient for characterization of the virus. Hence, the aim of this study was to develop a new PCR diagnostic technique specific to the ToHV.…”
mentioning
confidence: 99%